Unusual Vasospastic Angina: A Documented Asymptomatic Spasm with Normal ECG—A Case Report and a Review of the Literature - Ghassan Nakad; Hamid Bayeh (Case Reports in Cardiology)
We report the case of a 53-years-old patient, known to have coronary artery disease, presenting with typical angina at rest with normal ECG and laboratory findings. His angina is relieved by sublingual nitroglycerin. He had undergone a cardiac catheterisation two weeks prior to his presentation for the same complaints. It showed nonsignificant coronary lesions. Another catheterisation was performed during his current admission. He developed coronary spasm during the procedure, still with no ECG changes. The spasm was reversed by administration of 2 mg of intracoronary isosorbide dinitrate. Variant (Prinzmetal's) angina was diagnosed in the absence of electrical ECG changes during pain episodes.